IP3 receptor-mediated Ca2+ release from acidocalcisomes regulates mitochondrial bioenergetics and prevents autophagy in Trypanosoma cruzi. (December 2020) - Chiurillo, Miguel A.; Lander, Noelia; Vercesi, Anibal E.; Docampo, Roberto
Graphical abstract: Highlights: T. cruzi IP3 receptor (TcIP3 R) is located in acidocalcisomes of different stages. TcIP3 R is involved in Ca 2+ release from acidocalcisomes and mitochondrial integrity. Ablation of TcIP3 R was done using CRISPR/Cas9 gene editing. TcIP3 R -KO trypanosomes have reduced mitochondrial O2 consumption. TcIP3 R -KO trypanosomes have increased AMP/ATP ratio and autophagy. Abstract: In contrast to animal cells, the inositol 1, 4, 5-trisphosphate receptor of Trypanosoma cruzi (TcIP3 R) localizes to acidocalcisomes instead of the endoplasmic reticulum. Here, we present evidence that TcIP3 R is a Ca 2+ release channel gated by IP3 when expressed in DT40 cells knockout for all vertebrate IP3 receptors, and is required for Ca 2+ uptake by T. cruzi mitochondria, regulating pyruvate dehydrogenase dephosphorylation and mitochondrial O2 consumption, and preventing autophagy. Localization studies revealed its co-localization with an acidocalcisome marker in all life cycle stages of the parasite. Ablation of TcIP3 R by CRISPR/Cas9 genome editing caused: a) a reduction in O2 consumption rate and citrate synthase activity; b) decreased mitochondrial Ca 2+ transport without affecting the membrane potential; c) increased ammonia production and AMP/ATP ratio; d) stimulation of autophagosome formation, and e) marked defects in growth of culture forms (epimastigotes) and invasion of host cells by infective stages (trypomastigotes). Moreover, TcIP3 R overexpressing parasites showed decreased metacyclogenesis, trypomastigote host cell invasion and intracellular amastigote replication. In conclusion, the results suggest a modulatory activity of TcIP3 R-mediated acidocalcisome Ca 2+ release on cell bioenergetics in T. cruzi .